Inhibition of Vibrio anguillarum by Pseudomonas fluorescens AH2, a Possible Probiotic Treatment of Fish - Gram, Lone (American Society for Microbiology, 1999)
To study the possible use of probiotics in fish farming, we evaluated the in vitro and in vivo antagonism of antibacterial strain Pseudomonas fluorescens strain AH2 against the fish-pathogenic bacterium Vibrio anguillarum. As iron is important in virulence and bacterial interactions, the effect of P. fluorescens AH2 was studied under iron-rich and iron-limited conditions. Sterile-filtered culture supernatants from iron-limited P. fluorescens AH2 inhibited the growth of V. anguillarum, whereas sterile-filtered supernatants from iron-replete cultures of P. fluorescens AH2 did not. P. fluorescens AH2 inhibited the growth of V. anguillarum during coculture, independently of the iron concentration, when the initial count of the antagonist was 100 to 1,000 times greater that of the fish pathogen. These in vitro results were successfully repeated in vivo. A probiotic effect in vivo was tested by exposing rainbow trout (Oncorynchus mykiss Walbaum) to P. fluorescens AH2 at a density of 10(5) CFU/ml for 5 days before a challenge with V. anguillarum at 10(4) to 10(5) CFU/ml for 1 h. Some fish were also exposed to P. fluorescens AH2 at 10(7) CFU/ml during the 1-h infection. The combined probiotic treatment resulted in a 46% reduction of calculated accumulated mortality; accumulated mortality was 25% after 7 days at 12°C in the probiotic-treated fish, whereas mortality was 47% in fish not treated with the probiont.